A STUDY ON CONSUMER SHOPPING BEHAVIOUR TOWARDS RETAIL STORES IN NAGERCOIL TOWN (International Journal of Food and Nutritional Sciences, 2022)
Consumer behaviour is the most important to the retailers. It often involves the decision process with the retail phenomena. Consumers need the effective retail strategy and the development more than the competitors to understanding the need of the consumer satisfaction. The purpose of the study knows the thorough analysis of intention in shopping, habits of shopping and attitude of shopping of customers in the retail stores. The objectives are to identify the factors influencing the shopping of consumers towards retail stores and to analyse the attitude consumers in shopping towards retail stores. A stratified random sampling has applied and with the sample size of 75. Most of the respondents have problem in the inaccessibility in retail stores because of retail stores are far away from their residence. So retailers can setup many retail outlets as possible. The study shows that the consumers were triggered by ad and sales promotions. Based on the study the findings and suggestions will be an eye-opener for the retailers and it will help the retailers to get success in their sector.